DETERMINATION OF SOYBEAN (Glycine max L.[Merrill]) MICROSPORES DEVELOPMENT STAGE BASED ON THE LENGTH OF FLOWER BUDS - Sumarmi Sumarmi; Budi Setiadi Daryono; Diah Rachmawati; Ari Indrianto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
The number of published reports of flower buds, anthers and on microspore culture of horticultural plants, especially in soybean is very low. The purpose of this research is to determine soybean microspores development stage based on the length of flower buds. Five local cultivars such as Argomulyo, Grobogan,Wilis, Anjasmoro and the black soybean Malika were used. Flower buds were the main material for microspore culture. Anjasmoro cultivar produces the highest number of flower bud. Anjasmoro soybean cultivar at third stage development, 3.1-3.6 mm length, was selected for microspore culture, based on plant height, length of anther, total of microspore per bud. Anjasmoro cultivar has the most late-uninucleate microspore and the total of shed of Anjasmoro microspore in the B medium with 340C for 4 day is 3820. Results revealed that Anjasmoro soybean cultivars had 354.67±59.67 μm length of anther, 2003±216 microspore per bud and the most mid and late-uninucleat microspore on 2.6-3.6 mm length flower bud. Anjasmoro soybean cultivar can be used for microspore culture.